(untitled) (Research, Society and Development, 2022)
Nursing is a profession that is directly linked to assistance in the continuous care of people throughout life in the most diverse areas of care, also playing an important role in the process of population aging where there is a vast field to be explored. In this way, the present study aimed to analyze the role of nurses in Primary Health Care in approaching the vulnerable elderly, and how to improve care for this target audience. The method to be used referred to an integrative review. The search was carried out by searching the following databases: Latin American and Caribbean Science Literature, Scientific Electronic Library Online, Nursing Database and the Virtual Health Library. The keywords used followed the description of the terms Descriptors in Science in Health and Medical Subject Heading in English, Portuguese and Spanish. Initially, a table was built to expose the studies containing information such as year, title, authors, nature of the research, sample and results. After analyzing the articles, we can see that in Studies 1, 2, 3, 4 and 5, the lack of research by professional nurses on the healthy aging process was evidenced. Personal, social and environmental factors have consequences on the autonomy, self-care and self-esteem of the elderly, going beyond the delimitation of the absence or presence of diseases. Attention is paid to the fact that there is a concern about how to meet and apply specific health promotion models to this public in a more comprehensive way.